Identification and validation of cellular senescence-related genes and immune cell infiltration characteristics in intervertebral disc degeneration - Li, Hao; Miao, Lei; Wu, Jiayuan; Wang, Ye; Xia, Jiyuan; He, Da (Frontiers in Immunology, 2025)
ObjectiveTo identify cell senescence-related genes and immune cell infiltration characteristics in intervertebral disc degeneration (IVDD) using bioinformatics and investigate their biological functions and signaling pathways.MethodsGSE56081 and GSE23130 datasets were downloaded from the Gene Expression Omnibus (GEO) database. The former was used for the analysis of differentially expressed genes (DEGs) and the latter was used as the validation set. Intersection analysis of DEGs and cell senescence-related genes was performed to screen for senescence-related differentially expressed genes (SRDEGs). SRDEGs were analyzed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). A protein–protein interaction (PPI) network was also drawn, and the hub SRDEGs were obtained using 11 different algorithms. Immune infiltration analysis was then performed. Receiver operating characteristic (ROC) curve and quantitative polymerase chain reaction (qPCR) were used to evaluate the diagnostic value of the hub SRDEGs.ResultsFour hub SRDEGs, SP1, FOXO1, ESR1, and MAPK1, were identified. SP1 was downregulated in IVDD, while the other three hub genes were upregulated. ROC curve verification showed that the AUC for SP1, FOXO1, ESR1, and MAPK1 were 0.483, 0.683, 0.683, and 0.725, respectively. RT-qPCR confirmed that MAPK1 expression was higher in the degeneration group (t = 3.229, P <0.001). Immune infiltration analysis demonstrated elevated proportions of CD8 T cells and activated NK cells in IVDD samples, with MAPK1 showing positive correlations with CD8 T cells, activated NK cells, and neutrophils but negative correlations with naive CD4 T cells, B memory cells, and resting NK cells.ConclusionThese findings highlight MAPK1 as a pivotal regulator of cellular senescence and immune cell infiltration in IVDD pathogenesis, offering novel therapeutic targets for intervention.